Burkholderia glumae in the rice crop in Costa Rica. - Quesada-González, Andrea (2014)
The objective of this study was to determine the presence of B. glumae in the rice crop in Costa Rica. The bacterium Burkholderia glumae is associated with the cultivation of rice, causing the disease known as bacterial blight. Under favorable weather conditions, the bacterial density increases, thus causing the expression, under a system called quorum sensing regulation, of its virulence mechanisms, by activating genes responsible for toxoflavine synthesis, which blocks the flow of nutrients for flagellum biogenesis and the chemostatic response, and the production of the enzyme catalase. Plants develop symptoms that eventually lead to empty hulls, causing significant economic losses. The current level of contamination of rice seeds with this bacteria in Costa Rica was studied during 2009 and 2010, through an agreement between the National Rice Corporation, the Plant Pathology Laboratory of the Crop Protection Research Center at the University of Costa Rica. The Endpoint PCR methodology recommended by researchers at the International Center for Tropical Agriculture in Colombia, the identification was reinforced with conventional microbiology. Results indicating the presence of the bacteria in Costa Rica were obtained, providing the first information on the prevalence of a bacterial plant pathogen of great importance for the rice sector.